Circulating microRNAs in neuromuscular disorders - Mousa, Nahla (AUC Knowledge Fountain, 2020)
Identification of the mutations and genetic causes of the muscular diseases is performed for the muscular dystrophies, atrophies and other genetic diseases using current molecular high throughput techniques that precisely allocate the defected genes and detect the aberration in the expressed proteins responsible for any phenotype. For example, more than 2000 mutations in the DMD gene were identified in Duchenne Muscular Dystrophy patients or the milder form of the disease Becker Muscular Dystrophy. Detection of different mutation in the same gene has critical role as biomarkers in disease diagnosis, since the severity of the symptoms is usually associated with the location of the mutation on the gene. Also, detection of mutant proteins plays a critical role in disease diagnosis and revealing disease pathogenesis. In addition to DNA variations and proteins, circulating microRNAs are also used as surrogate markers in different disease conditions like cardiovascular diseases and cancer. microRNAs are endogenous epigenetic regulators of gene expression. Many studies reported the modulation in microRNAs expression in various body fluids at different pathophysiological conditions and hence they can be used as promising non-invasive diagnostic and prognostic biomarkers and most importantly they can be used as monitoring screen to detect the successfulness of therapeutic interventions since their expression status is dynamic and can change based on the physiological conditions and the behavior of the cells and the responsiveness to external stimuli. In the current work we aimed to identify potential Biomarkers in Neuromuscular disorders (NMDs) that may help in developing a diagnostic technique to facilitate the differential diagnosis for different forms of NMDs and to help in the identification of potential carriers.